Prevalence of Hepatitis C virus among Out-Patients of a Private Laboratory in Tehran - M Hajia; N Shahrokhi; AA Amirzargar; M Farzanehkhah; S Biglari; M Ghorishy; A Sarafnejad (Tehran University of Medical Sciences, 2007)
With an estimated 170 million infected individuals, hepatitis C virus (HCV) has a major impact on public health. Frequency of HCV infection was studied in 785 referred patients to a private Laboratory, Tehran, Iran from April 2003 until March 2006 by PCR method. Analyzed results revealed infection rate was 40.27%, 35.51% and 33.09% in the first, second and third year, respectively. Frequency rate of the infection shows a fluctuated shape during months of three years. Maximum rate of the HCV infection was in May of the first and in June of the second and third year, respectively. It shows decrease and increase within rest months in each year. HCV infection rate was higher in 31 to 40 years old group of patients. Analysis of the data revealed higher HCV infection in men than women had. It was concluded that HCV frequency pattern underlines specific attention to suspected patients during high rate time.